Collaboration Between Women and Child Protection and Women's Crisis Center in Assisting Victims of Sexual Violence Against Children - Mavitia Humairah Ms; Heni Nopianti; Ika Pasca Himawati (Journal of Law, Politic and Humanities, 2024)
This research is based on the issue of child sexual abuse, which is a problem in Indonesia, including in Bengkulu City; in response to this, government and non-government institutions must collaborate in assisting victims of child sexual abuse. This research aims to analyze the collaboration process between the Women and Child Protection Agency and the Women's Crisis Center in helping victims of child sexual abuse in Bengkulu City, analyzed using functional structural theory proposed by Talcott Parsons. This research uses a qualitative approach and is a descriptive research type. Data collection techniques used were non-participant observation, semi-structured interviews, and documentation. The results show that the collaborative mentoring process was carried out through several indicators: active online and offline communication and high trust and commitment between the two in solving problems. The deliberation stage is the hallmark of collaboration as community strengthening, which involves the community in preventing and handling cases. In some programs implemented, access to human resources is lacking, so collaboration can be established to achieve a more optimal service assistance process and the availability of financial resources from the central government. This study concludes that in addition to a smooth mentoring process, there are still obstacles, including the lack of evaluation and budget from the local government to support the smooth mentoring process.